Logic with trees: an introduction to symbolic logic - Howson, Colin 1945- (Routledge, 2005)
Logic with trees is a new and original introduction to modern formal logic. Unlike most texts on the subject, it includes discussions of more philosophical issues such as truth, conditionals and modal logic. Pre explanation and argument to intimidatingly rigorous development, Colin Howson presents the formal material in a clear and informal style that both beginners and those with some knowledge of formal methods will appreciate. Examples and exercises guide readers through the book, and answers to selected exercises at the end allow them to monitor their own progress. Logic with Trees gives students